2022
DOI: 10.1155/2022/3736104
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Validation of a Carvacrol-Targeting Viability-Regulating Protein, SLC6A3, in Liver Hepatocellular Carcinoma

Abstract: Background. Liver hepatocellular carcinoma (LIHC) is the second leading cause of tumor-related death in the world. Carvacrol was also found to inhibit multiple cancer types. Here, we proposed that Carvacrol inhibited LIHC. Methods. We used MTT assay to determine the inhibition of Carvacrol on LIHC cells. BATMAN-TCM was used to predict targets of Carvacrol. These targets were further screened by their survival association and expression in cancer using TCGA data. The bioinformatic screened candidates were furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…In the identi cation and characterization of immune molecular subtypes of LIHC, OXTR has been identi ed as a key player in liver cancer; and its overexpression in liver cancer tissues has been con rmed to affect prognosis 28 . SLC6A3 was identi ed as a key gene involved in the promotion of HCC cell proliferation and the initiation and progression of LIHC 29 . BIRC5 appears to be an independent, unfavorable prognostic biomarker in multiple types of tumors and has potential as a clinical target for future cancer therapies 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In the identi cation and characterization of immune molecular subtypes of LIHC, OXTR has been identi ed as a key player in liver cancer; and its overexpression in liver cancer tissues has been con rmed to affect prognosis 28 . SLC6A3 was identi ed as a key gene involved in the promotion of HCC cell proliferation and the initiation and progression of LIHC 29 . BIRC5 appears to be an independent, unfavorable prognostic biomarker in multiple types of tumors and has potential as a clinical target for future cancer therapies 30 .…”
Section: Discussionmentioning
confidence: 99%
“…For the rest of hub survival genes, there were 13 out of 15 genes which had consistent results with the findings of a previous study, of which for these survival favorable hub survival genes, immunohistochemistry assay identified that higher ADH4 protein expression was associated with favorable OS of HCC ( Wei et al, 2012 ); Overexpression of PRICKLE-1 ( Chan et al, 2006 ), FTCD ( Chen et al, 2019 ), and LINC01554 ( Hao et al, 2020 ) suppressed HCC cell proliferation; overexpression of TRIM55 inhibited migration and invasion of HCC cells ( Li et al, 2019 ); knockdown of CFHR3 promoted proliferation, migration, and invasion of HCC cells ( Wan et al, 2022 ); melatonin suppressed HCC progression via upregulation of lncRNA-CPS1-IT-mediated HIF-1α inactivation ( Wang et al, 2017 ). For these unfavorable hub survival genes, previous studies found that overexpression of CXCL8 in HCC cell resulted in increased cell proliferation and migration ( Yang et al, 2020 ); the impaired expression of GABRA3 ( Liu et al, 2008 ) and SPP1 ( Wang et al, 2019 ) decreased HCC cell viability; ITGBL1 increased KRT17 overexpression and promoted the metastatic ability of HCC cells ( Huang et al, 2020 ); nicotine stimulated CYP1A1 expression to promote HCC cell proliferation ( Ung et al, 2021 ); carvacrol inhibited the viability of HCC cells by downregulating SLC6A3 ( Yin et al, 2022 ). In summary, our study provided new insights between these genes and calpains and the prognosis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In the identi cation and characterization of immune molecular subtypes of LIHC, OXTR also has been identi ed as a key player in liver cancer, and its overexpression in liver cancer tissues has been con rmed to impact prognosis (28). SLC6A3 was identi ed as a key gene involved in the promotion of hepatocellular carcinoma cell proliferation and the initiation and progression of LIHC (29). BIRC5 appeared to be an independent unfavorable prognostic biomarker in multiple types of tumors and had the potential as a clinical target for future cancer therapy (30).…”
Section: Discussionmentioning
confidence: 99%